A Review on Solid Dispersion and Polymers Used For Solubility Enhancement through Lyophilization Technique - Suryawanshi Abhijeet,; Sawant Ganesh,; Dr. Prakash Jadhav,; Velhal Atish,; Bhongale Ashish,; Dr. Vivek kumar Redasani, (Asian Journal of Pharmaceutical Research and Development, 2025)
There are very few marketed treatments that use solid dispersions, despite their enormous potential to improve medication solubility. Solid dispersion has shown promise among the several techniques available to increase the new drug's solubility. Numerous hydrophilic carriers have been studied to improve the bioavailability and dissolving properties of medications that are not very soluble in water.It has been determined that solid dispersion is a better dose form for medications with low water solubility. Solid dispersions can be made using a variety of techniques, including lyophilization, hot melt extrusion, melt agglomeration, fusion, kneading, melting, solvent evaporation, fusion, spray drying, co-grinding, and supercritical fluid (SCF) technology. Pharmaceutical excipients that are utilized to make solid dispersions come in a wide variety of hydrophilic and hydrophobic carriers. This article provides an overview of the several types of natural, semisynthetic, synthetic, and modified hydrophilic carrier that are utilized to formulate solid dispersions through lyophilization technique.